2016
DOI: 10.1111/ppl.12445
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical and molecular characterization of an induced mutation conferring imidazolinone resistance in wheat

Abstract: The Clearfield(®) wheat cultivars possessing imidazolinone (IMI)-resistant traits provide an efficient option for controlling weeds. The imazamox-resistant cultivar Pantera (Clearfield(®) ) was compared with a susceptible cultivar (Gazul). Target and non-target mechanisms of resistance were studied to characterize the resistance of Pantera and to identify the importance of each mechanism involved in this resistance. Pantera is resistant to imazamox as was determined in previous experiments. The molecular study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…The greater I 50 value of ALS enzyme in the R wheat lines, Rados and Helter, indicates alterations in the target site. This suggests that the ALS‐ imi1 and ALS‐ imi2 resistant genes, with mutation Ser653–Asn from the imazamox‐resistant cultivar Pantera (parent), were transferred to the R wheat lines. Differences in imazamox susceptibility between the R lines, as demonstrated in ALS gene sequencing, were due to the Helter line acquiring both resistant genes (ALS‐ imi1 and ALS‐ imi2 ) from the Pantera cultivar, whereas the Rados line acquired only one (ALS‐ imi2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater I 50 value of ALS enzyme in the R wheat lines, Rados and Helter, indicates alterations in the target site. This suggests that the ALS‐ imi1 and ALS‐ imi2 resistant genes, with mutation Ser653–Asn from the imazamox‐resistant cultivar Pantera (parent), were transferred to the R wheat lines. Differences in imazamox susceptibility between the R lines, as demonstrated in ALS gene sequencing, were due to the Helter line acquiring both resistant genes (ALS‐ imi1 and ALS‐ imi2 ) from the Pantera cultivar, whereas the Rados line acquired only one (ALS‐ imi2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HR wheat lines Rados and Helter, each with multiple resistance to imazamox and glufosinate (IMA + GLU), came from crossing the glufosinate‐resistant T‐590 line (IAS/CSIC‐Cordoba, Spain) with the Clearfield® Pantera cultivar resistant to imazamox (INIA‐Carillanca, Chile). The Pantera cultivar has the Ser653–Asn mutation in the ALS‐ imi1 and ALS‐ imi2 genes . The T‐590 line contains the bar gene from pACH25 plasmid, which encodes the PAT enzyme …”
Section: Methodsmentioning
confidence: 99%
“…ance to the herbicide imidazolinone following introduction of the Ser-Asn627 mutation into two acetolactate synthase (ALS) genes (imi1 and imi2), located in wheat on chromosomes 6B and 6D, respectively, into cv. Pandora-INIA, by a biotechnological procedure 21 . In experiment 1, the average DW, GY and HI of Pandora-INIA and Pantera-INIA were not significantly different (P < 0.05), however, field experiments conducted in different environments showed consistently high GY in Pantera-INIA (http://www.semillasinia.cl/wp-content/uploads/2012/09/FolletoPanteraINIA.pdf 20 ;), indicating that the two cultivars probably respond differently to agronomic management.…”
Section: Plant Water-use Water-use Efficiency and Carbon Isotope Dismentioning
confidence: 99%
“…In wheat, IMI resistance genes were obtained by seed mutagenesis (Newhouse et al, 1992;Jimenez et al, 2016). IMI-R wheat cultivars have been marketed under the trade name 'Clearfield'(CL).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that two resistance genes (AhasL-D1 and AhasL-B1) were adequate for providing high levels of field resistance to the IMI herbicides . The basis of resistance is due to the presence of an altered form of AHAS that is resistant to inhibition by IMI herbicides but the presence of additional resistance mechanisms such as herbicide metabolism were also suggested for some cultivars (Jimenez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%